2019
DOI: 10.1101/795773
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Electroencephalographic evidence for the involvement of mirror neuron and error monitoring related processes in virtual body ownership

Abstract: The illusion that an artificial or virtual object becomes part of one's body has been demonstrated and productively investigated in the past two decades. Empirical and theoretical accounts of this phenomenon suggest that the body ownership illusion relies not on a single process, but rather on the alignment of the biological and the alternative bodies across multiple aspects. However, the portrayal of these aspects and the demarcation of their neurophysiological correlates has yet to be established.Our study e… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 83 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…We presume that performing training with cognitively demanding tasks could possibly have freed up cognitive resources required to maintain balance and eventually reduce cognitive motor interference that precipitates falls 112,113 . Moreover, studies have also speculated that the close biological proximity between virtual and real environment could also promote learning by facilitating activations in the frontoparietal mirror neuron system (MNS) 32,114–116 . Nevertheless, the evidence supporting the engagement of the MNS during virtual tasks is scarce and future work would be needed to establish its involvement with VR.…”
Section: Discussionmentioning
confidence: 99%
“…We presume that performing training with cognitively demanding tasks could possibly have freed up cognitive resources required to maintain balance and eventually reduce cognitive motor interference that precipitates falls 112,113 . Moreover, studies have also speculated that the close biological proximity between virtual and real environment could also promote learning by facilitating activations in the frontoparietal mirror neuron system (MNS) 32,114–116 . Nevertheless, the evidence supporting the engagement of the MNS during virtual tasks is scarce and future work would be needed to establish its involvement with VR.…”
Section: Discussionmentioning
confidence: 99%
“…Holroyd and Coles [7] proposed that an error-processing system in the ACC serves as reinforcement-learning signals to correct errors. Further studies have also shown that error-related potentials (ErrPs) spontaneously arise when users experience BiEs during avatar-based interaction in VR [4,[8][9][10][11][12][13]. These findings support the notion of an accumulation of errors in these conditions [14][15][16], where cognitive processes in embodiment contribute to a global error in user experience.…”
Section: Introductionmentioning
confidence: 55%
“…This manipulation often results in a sense of ownership over the fake hand, which was validated and replicated using various behavioural and physiological measures measurements (Riemer et al, 2019). Importantly, an illusion of ownership was successfully elicited toward virtual hands as well (IJsselsteijn, de Kort, and Haans 2006;Raz et al, 2019).…”
mentioning
confidence: 65%